2016
DOI: 10.18632/oncotarget.9340
|View full text |Cite
|
Sign up to set email alerts
|

Functional TRAIL receptors in monocytes and tumor-associated macrophages: A possible targeting pathway in the tumor microenvironment

Abstract: Despite the accepted dogma that TRAIL kills only tumor cells and spares normal ones, we show in this study that mononuclear phagocytes are susceptible to recombinant TRAIL via caspase-dependent apoptosis. Human resting monocytes and in vitro-differentiated macrophages expressed substantial levels of the functional TRAIL receptors (TRAIL-R1 and TRAIL-R2), while neutrophils and lymphocytes mostly expressed the non-signaling decoy receptor (TRAIL-R3). Accordingly, exclusively monocytes and macrophages activated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 63 publications
2
80
0
Order By: Relevance
“…Mechanistically, lurbinectedin activates caspase-8-dependent apoptosis in human monocytes within few hours and at low nanomolar concentrations. We previously demonstrated that the selectivity of trabectedin for the mononuclear phagocyte lineage relies on the fact that only monocytes and macrophages express appreciable levels of functional TRAIL-R, whereas neutrophils and T lymphocytes express high levels of the decoy non-signalling TRAIL-R3, and therefore are spared by the drug ( Germano et al , 2013 ; Liguori et al , 2016 ). In treated monocytes, trabectedin upregulates the transcription of TRAIL-R and this increase appears to be sufficient to trigger caspase-8 activation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, lurbinectedin activates caspase-8-dependent apoptosis in human monocytes within few hours and at low nanomolar concentrations. We previously demonstrated that the selectivity of trabectedin for the mononuclear phagocyte lineage relies on the fact that only monocytes and macrophages express appreciable levels of functional TRAIL-R, whereas neutrophils and T lymphocytes express high levels of the decoy non-signalling TRAIL-R3, and therefore are spared by the drug ( Germano et al , 2013 ; Liguori et al , 2016 ). In treated monocytes, trabectedin upregulates the transcription of TRAIL-R and this increase appears to be sufficient to trigger caspase-8 activation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes were purified through density gradients, as described ( Liguori et al , 2016 ). Cells were treated with lurbinectedin or trabectedin (2.5–10 n M ) for different time points as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, trabectedin and its second generation lurbinectedin are effective at killing TAMs in addition to cancer cells [153][154]. Mechanistically, trabectedin interacts with tumor necrosis factor-related apoptosis inducing ligand receptor 2 (TRAIL-R2) on mononuclear phagocytes leading to receptor clustering and subsequent caspase-8 dependent activation of apoptosis [154][155]. Its selective toxicity in TAMs over neutrophils and lymphocytes has been attributed to higher expression of the receptor in conjunction with lower expression of non-signaling decoy TRAIL-R3.…”
Section: Pharmacological Modulation Of Macrophages/tamsmentioning
confidence: 99%
“…Trabectedin is an European Medicines Evaluation Agency (EMEA)-approved natural product with antitumor activity (Germano et al 2010). Indeed, trabectedin activated the TRAIL-dependent apoptotic pathway selectively in monocytes, because of their low expression of TRAIL decoy receptors (Liguori et al 2016). In murine models and human sarcoma patients, trabectedin treatment resulted in a reduction of TAM infiltration and angiogenesis (Germano et al 2010), thus suggesting a promising role in TAM-targeted antitumor therapies.…”
Section: Roles Of Tams and Tans In Anticancer Therapeutic Responsesmentioning
confidence: 99%